APPLICATION OF INQUIRY LEARNING MODEL TO IMPROVE STUDENTS' ANALYTICAL THINKING ABILITIES IN ISLAMIC RELIGIOUS EDUCATION LESSONS AT SMP IT AL KHAIR SUNGGAL - Fitri, Elsya; Kamil, Kamil (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
Abstract Training on thinking skills is needed by students to improve their intellect.l Teachers need to apply a strategic or planning that is mature and in accordance with the goals of the students. The problem is that the Islamic Religious Education is a strategic inquiry that is used precisely to improve the ability to think, develop insight and improve the intellectual knowledge of students to nail the material around Islamic Religious Education. This study aims to find out how the Application of the Inquiry Learning Model to Improve Students' Analytical Thinking Skills in Islamic Religious Education Lessons at Al Khair Sunggal IT Junior High School? And the only advantages and disadvantages of the learning model inquiry. The research method uses qualitative methods. Based on the results of the research, the steps in implementing inquiry learning are by orientation, formulating problems, proposing hypotheses, collecting data, testing hypotheses, and formulating conclusions. The advantages of the application of inquiry learning are emphasizing learning strategies through the development of several cognitive, affective, and psychomotor aspects so that it can produce meaningful learning. Meanwhile, the drawback is that it is difficult to control students' activities and success. Keywords: Inquiry Learning Model, Analytical Thinking, Islamic Religious Education